SPEECH ACTS IN THE VIDEO SCRIPT OF AN ATHEIST CONVERTING TO ISLAM BY LAMPU ISLAM YOUTUBE CHANNEL - Amelia Balqis Siregar; Efendi Barus (JOURNAL OF LANGUAGE, 2021)
This research  was conducted to examine speech act in the video script of Lampu Islam Youtube Channel. The edition of the video is entitled An Atheist Converting to Islam. This study aims to answer the problem about the classification of speech act found in the video script. This research applied the theory of speech act proposed by Austin and further developed by Searle. There are three types of speech act. The classification involves locutionary, illocutionary and perlocutionary acts. The result of the research shows that all the type of Speech Act can be found in the video script. The utterances which belong to locutionary act reach four (4) occurrences. For illocutionary, there are two (2) utterances. Then, the utterances of perlocutionary acts occur most dominantly with sixteen (16) occurrences. Perlocutionary act reaches 62.5% occurrences in the video script. From the analysis, it can be concluded that the script is intended to give an effect to the listeners of the channel and to offer ideas to other people.